Trocar-site hernia repair after laparoscopic surgery: a case report study. Issue 3 (10th March 2023) - Bangeas, Petros; Hatzikomnitsa, Paraskevi; Karatzia, Despoina; Mauromatidis, Savvas; Papadopoulos, Vasileios
Abstract: Tracer site hernias (TSHs) are extremely uncommon. There have been only a few cases reported in the literature. Here we report a case of TSH after umbilicus laparoscopic hernia repair procedure. Diagnosis was based on patient symptoms and computed tomography. Patient underwent exploratory laparoscopy followed by laparoscopic hernia repair with mesh. We also provide a mini review of the literature in order to highlight that although rare, this pathology should be included in the differential diagnosis of acute abdomen.